Four decades of independence: The multiple cultures of Portuguese-speaking Africa - Rothwell, P; Martinho, A (American Portuguese Studies Association, 2016)
In the four decades since the independence of Portugal’s African colonies, the world has changed in ways that in the 1970s could scarcely have been imagined. The Cold War politics that lurked in the background of the 1960s struggles for independence took center stage in the 1970s and 1980s as Mozambique and Angola stumbled into civil wars that fused with proxy-conflicts between the USA and USSR. Cabo Verde and Guinea-Bissau’s improbable joint statehood ruptured in 1980, and the two political entities took very different paths that reflected very different experiences of colonialism. For its part, São Tomé e Príncipe initially followed a socialist trajectory, nationalizing the plantations, before a post-Cold War constitution heralded multiparty politics underpinned by capitalism.